Pharmacological treatment strategies for neonates with patent ductus arteriosus: a systematic review - Oliver Emmanuel Yausep; Adhi Teguh Perma Iskandar (Indonesian Pediatric Society, 2019)
Background Patent ductus arteriosus (PDA) has a variety of treatment options, ranging from pharmacologic, with nonsteroidal anti-inflammatory drugs (NSAIDs) as first line therapy, to surgical ligation. However, treatment with NSAIDs is associated with severe side effects as well as many contraindications. Paracetamol is a non-classic NSAID with the prospect of fewer side effects compared to other NSAID counterparts. Objectives To compare the efficacy and safety of paracetamol to ibuprofen or indomethacin for neonates with PDA by systematic review of the literature. Methods Our literature search was conducted on four databases: PubMed, Scopus, Ovid, and The Cochrane Library, to find studies that compared paracetamol to ibuprofen or indomethacin in neonates with PDA. Articles were selected based on pre-set eligibility criteria. Outcomes extracted from each study included PDA closure rates as well as adverse events rates. Results Seven randomized controlled trials (RCTs) were included in this study. Five compared paracetamol to ibuprofen and one used indomethacin as a control. The studies were of good quality, with several variations in methodology. All trials reported similar closure rates of paracetamol compared to ibuprofen or indomethacin. Three studies reported similar rates of adverse events, whereas another three reported safety profiles that favoured paracetamol over ibuprofen. Conclusion Paracetamol has similar efficacy to ibuprofen and indomethacin with regards to rate of PDA closure following a course of treatment. Paracetamol is also reportedly relatively safe in terms of adverse events rates experienced by patients.